TINGKAT KEPUASAN KONSUMEN K2B CAFE DI KOTA MANADO (Consumer Satisfaction Level K2B Cafe in Manado City) - Maria Kristina Purba; Yolanda Pinky Rori; Oktavianus Porajouw (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
This study aims to measure the level of K2B Cafe consumer satisfaction inManado City in terms of product, price, place, promotion, and service aspects. This research was conducted from January to May 2020. This study used primary and secondary data with accidental sampling techniques and 30 respondents withLikert Scale as the measurement instrument. The results showed that the level of K2B Cafe consumer satisfaction in Manado City was 78.11% with satisfied interpretation. Specifically, the level of customer satisfaction K2B Cafe for the very satisfied category is the variable price of 85,11% and promotion of 84.33%. For the satisfied category, product variable is 79.77%, place is 74.16%, and service is 74.33%.Keywords: Consumer Satisfaction Level, K2B Cafe, Manado City